A multiscale model to study the enhancement in the compressive strength of multi-walled CNT sheet overwrapped carbon fiber composites. (1st July 2019) - Ravindranath, Pruthul Kokkada; Roy, Samit; Unnikrishnan, Vinu; Wang, Xuemin; Xu, Tingge; Baughman, Ray; Lu, Hongbing
Abstract: The high tensile strength of polymer matrix composites is derived primarily from the high strength of the carbon fibers embedded in the polymer matrix. However, their compressive strength is generally much lower due to the fact that under compression, the fibers tend to fail through micro-buckling well before compressive fracture occurs. In this work, we consider multi-walled carbon nanotube (MWNT) sheets wrapped around carbon fiber at room temperature to improve fiber/matrix interfacial properties which, in turn, influences compressive strength of the composite. To investigate the effect of the wrapping of MWNT sheet on composite strength, Molecular Dynamics simulations were performed on an atomistic model of the interface region between the epoxy, carbon fiber and the scrolled MWNT sheets. The compressive strength of the unidirectional composite was computed using a novel hierarchical multi-scale model comprising of the rule of mixtures at the microscale, and the modified Argon's formula for composites at the macroscale. Model predictions were benchmarked through comparison with experimental data for different volume fractions of MWNT sheet.